Tinjauan Yuridis terhadap Netralitas Penyelenggara Negara dalam Pilkada Serentak Kabupaten Serang Tahun 2024 berdasarkan Undang-Undang Nomor 10 Tahun 2016 (Studi Kasus di Bawaslu Kabupaten Serang) - alvina lili nurlita (CV Rewang Rencang, 2025)
This research aims to analyze the underlying considerations of the judges in the Constitutional Court Decision Number 70/PHPU.BUP-XXIII/2025 and to examine law enforcement and oversight challenges in the 2024 Serang Regency Simultaneous Regional Elections based on Law No. 10 of 2016. The main focus is on violations of the neutrality of state apparatus that are structured, systematic, and massive (TSM), accompanied by political intervention and weak oversight coordination. It employs a normative legal method with a qualitative approach. The research results indicate the existence of TSM violations involving abuse of power by state officials, but law enforcement is hampered by the limited authority of the Election Supervisory Body (Bawaslu) and political intervention. This study recommends strengthening the role of the Constitutional Court, revising the Regional Election Law, and improving oversight synergy and legal protection for ASN to ensure democratic and accountable regional elections.